Analisis Kejadian Plasenta Akreta di RSUP H. Adam Malik Medan Tahun 2016-2019 - Dwi Putri, Savira; Helmi Effendi, Iman; Yulfi, Hemma; Ardiansyah, Edy (CV RIFAINSTITUT, 2022)
Placenta accreta is considered a life-threatening condition and is a cause of maternal death. Placenta accreta causes 7% -10% of cases of maternal mortality worldwide. Previous Sectio Ceasarea (SC) and uterine surgery are the most common risk factors for placenta accreta. Placenta accreta occurs when villous placenta invades directly into the myometrium. The incidence of placenta accreta increases with increasing incidence of SC. this wa is descriptive with a retrospective study. From 2016 – July 2019 there were 59 cases of placenta accrete with an increase in the number each year. Risk factor for the history of sectio ceasarea (94,8%). Sectio ceasarea + hysterectomy is a procedure of placenta accreta. There were no maternal mortality from 2016 – 2019 up to July. The annual incidence of placenta accreta increases each years mean risk factors dominant placenta accreta is history sectio ceasarea.